Sarcocystis lari ... - Gjerde, Bjørn; Vikøren, Turid; Hamnes, Inger Sofie (Zenodo, 2018)
3.3.3. Ribosomal DNA unit of S. lari The new sequence of the complete 18S rRNA gene from isolate Ha1.8 (GenBank no. MF 946588), which was 1804 bp long, was 100% identical with GenBank sequence JQ733508 of S. lari from sarcocysts in the great black-backed gull in Lithuania (Prakas et al., 2014). These sequences shared the highest identities with sequences of S. turdusi (99.8%), S. halieti, S. calchasi and S. wobeseri (99.7%); followed by those of S. corvusi and S. lutrae (99.6%). The new 1506-bp-long sequence of the partial 28S rRNA gene from isolate Ha1.8 (GenBank no. MF 946611) was 100% identical with GenBank sequence JQ733508 of S. lari from sarcocysts in the great black-backed gull, followed by an identity of 98.8% with sequences of S. calchasi (GenBank no. FJ 232949) and S. wobeseri (GenBank nos. GQ 922887, GQ922888, HM 159420, EF079886), and 98.6% identity with a sequence of S. turdusi (GenBank no. JF975682). The new sequence of S. lari was 98.3% identical with the new sequence of S. halieti. Concerning ... : Published as part of Gjerde, Bjørn, Vikøren, Turid & Hamnes, Inger Sofie, 2018, Molecular identification of Sarcocystis halieti n. sp., Sarcocystis lari and Sarcocystis truncata in the intestine of a white-tailed sea eagle (Haliaeetus albicilla) in Norway, pp. 1-11 in International Journal for Parasitology: Parasites and Wildlife 7 (1) on pages 6-7, DOI: 10.1016/j.ijppaw.2017.12.001, http://zenodo.org/record/10835073 ...